Comparative Genomics and CAZyme Genome Repertoires of Marine Zobellia amurskyensis KMM 3526(T) and Zobellia laminariae KMM 3676(T) - Chernysheva, Nadezhda (Mar Drugs, 2019)
We obtained two novel draft genomes of type Zobellia strains with estimated genome sizes of 5.14 Mb for Z. amurskyensis KMM 3526(Т) and 5.16 Mb for Z. laminariae KMM 3676(Т). Comparative genomic analysis has been carried out between obtained and known genomes of Zobellia representatives. The pan-genome of Zobellia genus is composed of 4853 orthologous clusters and the core genome was estimated at 2963 clusters. The genus CAZome was represented by 775 GHs classified into 62 families, 297 GTs of 16 families, 100 PLs of 13 families, 112 CEs of 13 families, 186 CBMs of 18 families and 42 AAs of six families. A closer inspection of the carbohydrate-active enzyme (CAZyme) genomic repertoires revealed members of new putative subfamilies of GH16 and GH117, which can be biotechnologically promising for production of oligosaccharides and rare monomers with different bioactivities. We analyzed AA3s, among them putative FAD-dependent glycoside oxidoreductases (FAD-GOs) being of particular interest as promising biocatalysts for glycoside deglycosylation in food and pharmaceutical industries.